Mad Conductors: Pathways of Attention and Dramaturgies of Care - Heit, Stephanie; Riley, Alexis (Performance Matters, 2025)
Mad Conductors is a participatory performance that arises out of a desire to transmute and transform personal experiences of electroshocks and psychiatric memory loss. It is an exploration of electricity, shock, connection, memory (loss), and collective mad ways of being. What happens when energy is transferred? Who or what conducts the ensemble? How can we hold memory as a community? How can we hold the gaps? What resources do mad ancestors and archives offer? In Mad Conductors, we investigate and play with these questions through writing, movement, doodling, sound, and other mediums we invent. Our engagements have happened in community settings, universities, nature, and especially with people with lived mad experiences. Together, we work to create supportive spaces to tend to ourselves and each other while we imagine and experiment with new openings, pathways, and futures of care.Our essay examines our collaboration as an embodied form of dramaturgy. While psychiatric memory loss can be (and often is) deeply painful, we also suggest that these experiences can point us toward new strategies for collectively holding and narrating memory. Accordingly, we structure our performance engagements not only in relation to our subject matter (psychiatric memory loss) but also in relation to the supports we need as mad collaborators to safely and joyfully engage this material. Rather than scripting a set production, we use our skills as artists to build a diverse range of containers, from participatory performances, university workshops, and house visits. While not necessarily conforming to conventional definitions of performance, we consider each engagement to be equally on par with the others; they are all Mad Conductors performances. The resulting project offers a flexible set of environments, actions, and modes of engagement, all while inviting participants into dramaturgical contact with mad forms of knowledge production.In this essay, we weave photos, questions, and responses from Mad Conductors events with individually authored vignettes addressing our personal experiences as both collaborators and friends. Taken together, this divergent compositional structure reflects the nonlinear, fragmentary, and partial qualities of memory loss, conveying alternate qualities of mad experience in both content and form—what we understand as a mad dramaturgical praxis.Plain Language Abstract (adapted by Kelsie Acton with Daniel Foulds)In Mad Conductors we invite the audience to work together to make the performance with us. We wanted to do this project because doctors shocked one of our brains with electricity. Electroconvulsive therapy is when doctors run electricity through someone’s brain to treat their mental health. But it often causes memory loss. We both have memory loss from the ways doctors treated our mental health. Now we want to make these experiences into art. We want to make art for other people with these experiences. Our project explores many themes:electricityshockconnectionmemory (loss)ways of being mad togetherOur project also asks many questions:What happens when energy moves from one place to another?Who or what tells a group of people how to move?How can a group of people remember together?How can we recognize and live with memory gaps?How can the people who were mad before us help us?How can old documents and records of mad people help us?In our Mad Conductors performances, we ask these questions throughwriting,movement,drawing,sound,other ways we make up.Our performances have happened inplaces where mad people are,universities,and nature.We work with other mad people to make our performances. As we create the performance together, we support ourselves and other people. We also try out new ways of caring.Our essay talks about working together through the lens of dramaturgy. This means that we are interested in how stories are told. Stories about the kinds of memory loss we have experienced are often painful. However, we believe that if we tell these stories in a different way, we could create new ways for making and sharing memories. Even when we can’t quite remember everything perfectly on our own. We think about this when wecreate performances with community members,teach workshops for college students,andvisit friends’ homes.All of these are Mad Conductors performances. We hope each one lets people experience the stories we tell in different ways.In our essay, we share photos, questions, and what people said from our Mad Conductors performances. We also share writing about working on the performances. We write about many topics. We ask a lot of questions. We don’t have many answers. We hope that these different ways of writing remind you of the way we don't remember everything. We also hope that these different ways of writing let you experience a new way of telling stories about memory loss.